Budaya Religius Dalam Pembentukan Karakter Peserta Didik Di SMP Islam Ulul Albab Nganjuk - Misfaf Abdul Azis; Ahmad Masrukin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This paper is to examine the religious culture of the character formation of students in Ulul Albab Islamic Middle School Nganjuk. This study departs from two research questions. "How is the implementation of religious culture in the Ulul Albab Nganjuk Islamic Middle School?", "What is the impact of religious culture in the Ulul Albab Nganjuk Islamic Middle School?". With these two questions the researchers found that first, religious culture is a culture with positive activities that contain Islamic religious values ​​that are very thick. While the religious culture of educational institutions is an effort to realize the values ​​of religious teachings as a tradition in behaviour and organizational culture that is followed by all citizens in educational institutions. The religious culture at Ulul Albab Islamic Middle School contains the implementation of tartil and tahfidz every morning, then continues with the Dhuha Praying in touch, at the time of Dzuhur students are required to pray in congregation, and the last is the implementation of a special mujahadah which is held once a month every 8th, in it contains Dhikr, prayers, and Sunnah Prayers. Second, the impact of the application of religious culture in Ulul Albab Nganjuk Islamic Middle School on the character of students includes the politeness of the students towards the teacher and those who are older than him, a sense of tolerance among friends, a reduction in the nature of bullying, so it is more disciplined with religious habituation, especially in religious habituation. matters of worship and students become more responsible.